A pilot and feasibility study of a cognitive behavioural therapy-based anxiety prevention programme for junior high school students in Japan: a quasi-experimental study - Ikuyo Ohira; Yuko Urao; Yasunori Sato; Toshiyuki Ohtani; Eiji Shimizu (BMC, 2019)
Abstract Background There is a good deal of evidence that cognitive behavioural therapy is effective for children and adolescents with anxiety-related problems. In Japan, an anxiety prevention programme based on cognitive behavioural therapy called 'Journey of the Brave' has been developed, and it has been demonstrated to be effective for elementary school students (aged 10-11 years). The purpose of this study was to have classroom teachers deliver the programme to junior high school students (aged 12-13 years) and to test the feasibility and efficacy of the programme in this setting. Methods This study was a prospective observational study and was approved by the Chiba University Review Board. An intervention group consisting of six classes of students in their first year of junior high school at two different schools (n = 149; 81 boys, 68 girls) received seven 50-min programme sessions. Participants in the control group were recruited from four classes of students in their second year of junior high school at one school (n = 89; 51 boys, 38 girls). All participants completed the Spence Children's Anxiety Scale at pre-test, post-test, and 2-3 month follow-up. Statistical analysis was conducted using a mixed-effects model for repeated measures model. Results Mean total anxiety scores indicated a non-significant decrease at the 2-3 month follow-up for the intervention group compared to the control group. The group differences on the SCAS from baseline to post-test was − .71 (95% CI − 2.48 to 1.06, p = .43), and the 2-3 month follow-up was − .49 (95% CI − 2.60 to 1.61, p = .64). Conclusions In this pilot study, implementation of the programme confirmed the partial feasibility of the programme but did not elicit a significant reduction in anxiety scores. In addition, there are several methodological limitations to this study. In the future, we propose to test the feasibility and efficacy of the programme with the required sample size and by comparing groups with equal characteristics as well as by carrying out additional follow-up assessments. Trial registration UMIN000032517.